Agronomic performance of male-sterile and fertile maize genotypes at two plant populations Performace agronômica de genótipos macho-estéreis e férteis de milho em duas densidades de semeadura - Luís Sangoi; Ricardo Salvador (Ciência Rural, 1996)
This experiment was conducted in 1994 at Ames, Iowa, US to test whether cytoplasmic male-sterility can be used to decrease barrenness and to increase grain yield of maize at two plant populations. Four genotypes were tested: a hybrid (NK 6330) and an inbred, wifh sterile and fertile counterparts. Each genotype owas evaluated at plant populations equivalent to 25,000 and 75,000 pl. ha-1. Hybrids produced higher grain yield than inbreds at both plant populations. Gram yield was higher at 75,000 than at 25,000 pl. ha-1. No difference in gram yield, number of ears per plant, number of grains per ear, tassel length, and tassel number of branches was found between sterile and fertile counterparts of the inbred and hybrid, regardiess of plant population. Fertile genotypes bore heavier tassels at anthesis than their sterile counterparts. Adequate precipitation distribution and high fertility level in the soil probably decreased competition between tassel and ears, mitigating potential yield benefits of suppressing genetically pollen production. Este experimento foi conduzido em Ames, Iowa, US durante o ano agrícola de 1994, tendo como objetivo avaliar se a macho-esterelidade genético-citoplasmática pode ser utilizada para aumentar o rendimento de grãos de milho em diferentes populações de planta. Quatro genótipos foram utilizados: um híbrido (NK 6330) e uma linhagem, ambos em suas versões fértil e macho-estéril. Cada genótipo foi avaliado em duas densidades de semeadura, equivalentes a 25.000 e 75.000 pl.ha-1. Os híbridos produziram maiores rendimentos de grão do que as linhagens nas duas populações utilizadas. O rendimento de grãos por área foi maior em 75.000 do que em 25.000 pl.ha-1. Nenhuma diferença significativa em termos de rendimento de grãos, número de espigas por planta, número de grãos por espiga, comprimento e número de ramos do pendão, foi observada entre genótipos férteis e macho-estéreis, independentemente da população de plantas. As versões férteis apresentaram pendões mais pesados do que os genótipos macho-estéreis. A adequada distribuição da precipitação e a alta fertilidade do solo possivelmente diminuíram a competição entre o pendão e as espigas, minimizando os benefícios da supressão genética da produção de pólen sobre o rendimento de grãos.